THE USE OF STEREOTYPICAL IMAGES OF AFRICA IN FUNDRAISING CAMPAIGNS - Dolinar, Maja; Sitar, Polona (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿This article critically examines Unicef’s campaign in Slovenia, aimed at helping children in Ruanda, which caused huge public support in terms of the raised finances and visibility, but it also provoked a serious opposition from African people living in Slovenia and some academics. The article investigates the role of negative stereotypical consequences of such African images. The method of our research was a detailed visual analysis of the campaign including profound interviews with different parties that gave us their point of view. The campaign was financially very successful, especially because of the big media coverage. The marketing company had no ethical hesitations in designing this campaign, although they received some hindrances from the Slovenian African Centre. The main goal was to raise as much money as possible to help these children, but helping in this way has never enabled Africa to develop into an independent continent. One article, which may present a true image of a certain area, is not problematic, but a continuous representation of only one image can lead to stereotypes that trigger discrimination. The Slovenian public received a confused, muddled and incomplete picture of Africa, because the images were taken out of context and portray the whole continent as helpless and in need of the ‘West’ to prosper. The used images consolidate the status quo of the European superiority. Overall, that kind of analysis can provide useful insights into some of the strategies for a more positive image of Africa in the future.